Validation of the applicability of the particle-based open-source software DualSPHysics to violent flow fields. Issue 4 (2nd October 2021) - Sato, Kenta; Kawasaki, Koji; Watanabe, Ken; Koshimura, Shunichi
ABSTRACT: Emerging as powerful open-source software in recent years, "DualSPHysics" is receiving increased attention for its ability to simulate large-scale flow fields. In the context of applying open-source software, the differences in the numerical results due to different model parameters need to be investigated in detail. In this study, some benchmark problems have been solved with DualSPHysics to validate the estimation of wave impact pressure with violent breaking waves. We have demonstrated three main results: (i) as an alternative to the artificial viscosity traditionally used in DualSPHysics, a laminar viscosity model can also well reproduce the solutions to the existing benchmark problems in a violent flow field with the modified dynamic boundary condition; (ii) the dynamics of the gas phase is essential in the calculation of wave breaking with rapid gate opening; and (iii) if the density diffusion parameter is too large, the impact pressure may be underestimated. The practical contribution by this study is to find that DualSPHysics well reproduces complex breaking waves, including multi-phase gas-liquid flows, and that the wave impact pressure is accurate by comparison with existing experimental results. This allows us to understand the complex behavior of fluid-structure interactions in coastal engineering by means of DualSPHysics.